Analisis Semiotik Dalam Cerpen “Dilarang Menyanyi Di Kamar Mandi” Karya Seno Gumira Ajidarma - Meti Novia; Santi Faujiah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
The short story "Dilarang Menyanyi di Kamar Mandi" by Seno Gumira Ajidarma is a captivating work of literature that captures the attention of readers and researchers due to its profound potential for semiotic analysis. This analysis helps us delve into deeper meanings and understand how the author uses signs and symbols to convey significant messages within the short story. Furthermore, semiotic analysis allows us to comprehend the author's thoughts and worldview. This article provides a detailed exploration of the semiotic analysis approach used in the short story, revealing the complexity of this literary work and how semiotic elements are employed to convey profound messages and meanings. The theoretical framework includes an introduction to Peirce's semiotic theory as the basis for the analysis, while the research methodology offers a clear perspective on the analytical process. The conclusion emphasizes the importance of semiotic analysis in understanding literature and enriching our understanding of "Dilarang Menyanyi di Kamar Mandi" as a form of literature that touches on profound aspects of humanity and society. This research has the potential to serve as a foundation for further studies on semiotic theory in literature.